La conservazione dell'Orso bruno ( Ursus arctos ) in Appennino: il supporto della genetica non invasiva - Rita Lorenzini; Mario Posillico; Leonardo Gentile; Rosario Fico; Luciano Sammarone (Associazione Teriologica Italiana, 2005)
Abstract Conservation of the brown bear Ursus arctos in the Apennines: a noninvasive genetic approach Molecular techniques were used to assess individual identification for 24 brown bears ( Ursus arctos ) from the Apennine population through noninvasive sampling. Shed hairs were collected and used as a source of DNA to derive single genotype profiling at 12 microsatellite loci. Genotypes of 11 bears were obtained from tissues or blood of dead or caught animals. Average expected heterozygosity (H E = 0.432) and mean number of alleles per locus (n A = 2.1) showed that the level of genetic diversity was one of the lowest recorded for brown bear populations across their European and North American ranges. A large portion of the original genetic variation may have gone lost through random genetic drift during the recent period of isolation. However, the level of genetic variability proved sufficient to identify the bears individually using 9 microsatellite loci. The probability that two animals shared by chance the same multilocus genotype was estimated to be 1 in 100. Lack of genetic diversity, as well as the maintenance of an adequate effective number are alarming and may seriously jeopardize the long-term survival of this population. Furthermore, high mortality rates, poaching and encroachment with human activities represent immediate, urgent concerns. In a conservation perspective, we suggest to implement protection and enforce habitat restoration for a natural increase of the population. Presently, restocking with bears from other source populations should be discouraged to avoid genetic extinction of the resident bears. Noninvasive sampling provided reliable population and individual genetic data without disturbing the animals, and microsatellite genotyping proved a valuable genetic tagging method and a feasible alternative to conventional field counts. Riassunto Ventiquattro individui di orso bruno ( Ursus arctos ) appenninico sono stati identificati singolarmente attraverso metodi molecolari, a partire da ...